The effects of corporate social responsibility practices on organizational performance among the commercial banks in Bangladesh / \c Mohammad Zahir Raihan. - Raihan, Mohammad Zahir (School of Business Innovation and Technoprenurship, Universiti Malaysia Perlis, 2018)
This study explores the effect of CSR practices on organizational performance among the commercial banks in Bangladesh in terms of financial performance and corporate image building. To fulfill the broad objective of the study, the specific objectives are as follows ; to find out the effects of CSR practices on 'financial performance' of commercial banks in Bangladesh ; to investigate the effects of CSR practices on the 'corporate image building' of commercial banks in Bangladesh ; to determine the moderating effects of government policy on the relations between CSR practices and financial performance ; to examine the moderating effect of government policy on the relationship between CSR practices and corporate image building.